2017
DOI: 10.1371/journal.pone.0172699
|View full text |Cite
|
Sign up to set email alerts
|

Increased breakdown of kynurenine towards its neurotoxic branch in bipolar disorder

Abstract: IntroductionBipolar disorder (BD) is a chronic psychiatric disease which can take most different and unpredictable courses. It is accompanied by unspecific brainstructural changes and cognitive decline. The neurobiological underpinnings of these processes are still unclear. Emerging evidence suggests that tryptophan catabolites (TRYCATs), which involve all metabolites of tryptophan towards the kynurenine (KYN) branch, are involved in the etiology as well as in the course of BD. They are proposed to be mediator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 40 publications
(47 reference statements)
1
52
1
1
Order By: Relevance
“…In line with our findings, studies using peripheral blood samples showed unchanged or decreased KYNA levels in patients with a history of mania or psychosis . Decreased peripheral KYNA levels have also been shown in euthymic and depressive patients with BD . As further discussed below, this discrepancy between central and peripheral results may reflect the difficult passage of KYNA across the blood–brain barrier (BBB).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In line with our findings, studies using peripheral blood samples showed unchanged or decreased KYNA levels in patients with a history of mania or psychosis . Decreased peripheral KYNA levels have also been shown in euthymic and depressive patients with BD . As further discussed below, this discrepancy between central and peripheral results may reflect the difficult passage of KYNA across the blood–brain barrier (BBB).…”
Section: Discussionsupporting
confidence: 88%
“…8,12,16 Decreased peripheral KYNA levels have also been shown in euthymic and depressive patients with BD. 16,20,21 As further discussed below, this discrepancy between central and peripheral results may reflect the difficult passage of KYNA across the blood-brain barrier (BBB). Secondly, a negative correlation between inflammatory markers and the neuroprotective ratios are found in patients only and appear across all mood states.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rats receiving intrastriatal injections of quinolinic acid experience alterations of microtubule-associated protein-2 and cytoskeletal disruption (95). Another tryptophan metabolite, 3hydroxykynurenine, can cause hallucinations and is thought to play a role in the development of schizophrenia and bipolar disorder (96,97). High levels of 3-hydroxykynurenine correlate strongly with increased schizophrenic symptoms.…”
Section: Tryptophan Fluorescencementioning
confidence: 99%